2016
DOI: 10.1139/cjas-2015-0190
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and variability of short-term spot measurement of methane and carbon dioxide emissions from beef cattle using GreenFeed Emissions Monitoring System

Abstract: The purpose of this study was to determine the repeatability of methane (CH 4 ) and carbon dioxide (CO 2 ) emissions from beef cattle using GreenFeed emissions monitoring (GEM) system and as affected by sampling frequency and measurement periods. Twenty-eight crossbred replacement beef heifers were monitored using the GEM system over 59 d to collect their CH 4 and CO 2 emissions data. Heifers' feed intake was recorded by eight automated feeding stations. The standardized dry matter intake (SDMI), CH 4 and CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
46
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 23 publications
12
46
2
4
Order By: Relevance
“…Therefore, the highest number of measurements were obtained between 17:00 to 20.59. A diurnal pattern was observed for CH 4 emissions (Table 4), which is consistent with other studies [9,14,15]. Across feeding systems, emissions were lowest between 05:00 and 08:59, which would relate to a typical time to allocate feed to dairy cows, after which emissions increased to a peak concentration between 17:00 to 20.59.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Therefore, the highest number of measurements were obtained between 17:00 to 20.59. A diurnal pattern was observed for CH 4 emissions (Table 4), which is consistent with other studies [9,14,15]. Across feeding systems, emissions were lowest between 05:00 and 08:59, which would relate to a typical time to allocate feed to dairy cows, after which emissions increased to a peak concentration between 17:00 to 20.59.…”
Section: Resultssupporting
confidence: 88%
“…A number of studies have demonstrated techniques for obtaining measurements of CH 4 emissions from individual cattle in their normal environment using repeated spot measurements [9,[11][12][13]15,18]. The positive correlation between spot measurements of CH 4 obtained during milking and total daily CH 4 emissions by the same cows when housed subsequently in respiration chambers in a previous study [10], and the ability of the technique to detect the effect of diet [10,24], has led to considerable research into the spot measurement technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 8-12-week testing period, over 200 spot measures per heifer were obtained on average for calculating the daily gas emission rates. This amount of spot measures was well above the minimum numbers, 20 to 50, recommended by several authors [23][24][25][26] for the precise measurement of CH 4 and CO 2 with GreenFeed systems. The CH 4 averages were very similar in the two heifer populations: 205 g/d on average, while CO 2 was lower for Borculo heifers compared to Galle heifers (6139 vs. 6918 g/d) as expected, due to their lower daily gain.…”
Section: Recorded Traitsmentioning
confidence: 51%